Computer-aided design of microfluidic very large scale integration (mVLSI) biochips : design automation, testing, and design-for-testability /: design automation, testing, and design-for-testability. (2017) - Hu, Kai; Chakrabarty, Krishnendu; Ho, Tsung-Yi
No abstract available